EN to RN: The transition experience pre-and post-graduation - Rapley, Pat; Nathan, Pauline; Davidson, Laura (Rural and Remote Health, 2006)
The context for this study is a conversion program for enrolled nurses (ENs) or division 2 level nurses who want to further their career as a registered nurse (RN) or division 1 nurse. While the conversion program is available to both metropolitan and rural nurses, it is designed specifically for experienced rural ENs. The conversion program is able to offer an educational alternative that does not disrupt family life or adversely impact the rural nursing workforce. This alternative is necessary for both the rural EN's career opportunities and for the health outcomes of rural communities in particular. This article reports on the experiences of the first cohort to graduate from the EN to RN conversion program. The conversion program offers three semesters of advanced standing within a seven-semester Bachelor of Science (Nursing) degree. The advanced standing or recognition of prior learning is awarded to applicants with more than one year's clinical experience, regardless of the type of enrolled nurse course completed. Enrolled nurses with a technical college qualification or higher meet university entry criterion but students from a hospital-based program are required to complete a mature-age university entry test. The degree to which the three semesters of advanced standing within an external conversion course for ENs would adversely affect participants' transition to student status and course completion is not known. The conversion program: The two-year, fully external EN conversion program relies on learning centre partnerships with country hospitals and agencies. Teaching strategies consist of a mix of external-mode strategies, including fully web-based units, and a compulsory eight-day on-campus foundation study block at the beginning.The compulsory study block provides the opportunity for students to familiarise themselves with the various areas of the university they need to contact as an external student, prepare for expectations of their first unit, including assessment expectations, and to practise selected nursing skills that are not common to the EN role. With the program being delivered from the metropolitan area of a vast state that occupies one-third of the Australian landmass, a key feature is the establishment of rural learning centres to support students. Apart from two of the seven clinical units in their course, the designated rural academic mentors arrange clinical placements in school-approved health care agencies situated locally or in nearby towns. This later strategy avoids the necessity for students to relocate to the metropolitan area or larger towns to complete the clinical component of the course. The conversion program has enrolled a limited number each year since 2000 and continues to be in high demand. Rural EN's are given preference and metropolitan enrolled nurses are included when quota allows. Purpose: The purpose of this article is to describe the two aspects of the transition experiences of graduates from an external conversion degree. First, their transition experience from experienced enrolled nurse to undergraduate student and, second, from graduate to novice RN. Participants: Participants were volunteer graduates from the Bachelor of Science (Nursing) two-year conversion degree. The 10 study participants were mature-age females, aged between 33 and 53 years (mean = 42 years). Five were from rural areas. Their educational background included hospital-based diploma or technical college certificate.Method: Data were collected using open-ended questions in semi-structured interviews. The interviews were transcribed and thematic analyses of the data were undertaken. Major categories were identified and relationships among them detailed. Results: The four categories identified included adjusting to higher education, achieving academically, becoming critical thinkers and adjusting to the RN role: accepting responsibility. Participant responses in this study have highlighted the necessity for timely responses to email, feedback on assignments and more mentor support for rural students during the course. Participants report changing the way they approached their nursing practice.Conclusions: The transition experiences for participants in the external conversion program are generally positive although, as with other studies, the transition to student status is stressful. However, the course is able to facilitate the career aspirations of the study participants and to contribute to the retention of nursing staff in rural areas. Strategies to provide career opportunities for health-care professionals in rural areas are always a challenge. As one such strategy, the external mode EN to RN conversion program has proven to be effective for experienced EN's.